Mapping and analysis of the supply chain: a case study in footwear industry - Nunes, Paloma dos Santos Alves; Souza, Karla Isabelle de; Bezerra, Camila Alves; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2023)
Given the current scenario of intense competition among organizations in the market, performing well-structured planning becomes increasingly important for the survival and success of organizations. In this sense, supply chain management allows for coordinated management of the relationships between partner organizations, in order to create value for products and services, reducing associated costs. The present study was conducted in a footwear industry located in the state of Paraíba and aimed to map and analyze the organization's supply chain, aiming to build structures that allow a systemic view of suppliers and customers, enabling better management and control over production and logistics processes. For this purpose, data collection was carried out both in the organization under study and in partner organizations, focusing on the analysis of relationships and their specific characteristics. The results allowed mapping and analyzing the organization's supply chain based on several aspects, enabling an oriented management and better control of associated logistic risks.
Keywords: Supply chain management; Logistics; Lead Time; Distribution management